Morphological Evolvement of Carbon Nanotubes Synthesized by Using Conducting Polymer Nanofibers. (2nd March 2020) - Liu, Yang; Xin, John H.; Zhang, Xinyu; Zhang, Chao
Abstract : Carbon nanotubes were synthesized by using a nanostructured conducting polymer—the polypyrrole nanofiber via microwave radiation. The radiation time was set to be 30, 60, and 90 seconds, respectively. The morphological evolvements of the as-synthesized carbon nanotubes with increased radiation time (e.g., shape, diameter, wall structure, and catalyst size) were carefully investigated, and the possible growth mode was discussed in detail. It was found that the growth mode of the carbon nanotubes synthesized from the conducting polymer substrate under microwave radiation was complex and cannot be simply interpreted by either a "tip" or "base" growth model. A new growth mode of the "liquifying cascade growth" was observed for the as-synthesized carbon nanotubes, as their growth was directed by a series of liquified iron nanoparticles with sequentially decreasing sizes, similar to the cascade of liquid droplets. And it could provide useful insights for the morphological and structural designs of the carbon nanotubes prepared by related microwave-based methods.